Students Attitude Towards LGBTQ; the Future Counselor Challenges - Zadrian Ardi; Frischa Meivilona Yendi; Ifdil Ifdil (Jurnal Konseling dan Pendidikan, 2017)
The condition of sexual disorientation behavior is a condition that develops from various and interrelated factors. This behavior is not the result of a single major factor, its formation occurs throughout the individual life span instead. The sexual behavior disorientation is a phenomenon that is always happening almost in all communities in various countries, which in the modern world popular with the term LGBTQ (Lesbian, Gay, Bisexual, Transgender and Queer). Another condition related to this community is that in recent years human rights related to this matter have been straightforwardly defended in some countries. This condition brings many problems and polemics in various dimensions of life. This study focuses on the trend of student attitudes toward LGBTQ phenomena that in the society. Data were collected through a student's attitude scale on the LGBTQ phenomenon adapted from "Worthen's (2012) Attitudes toward LGBT People Survey" and involving 213 respondents. Students in West Sumatera generally have an unfavorable attitude towards the LGBTQ phenomenon. But in one aspect, students have a moderate attitude towards the transgender phenomenon. This has become an important concern for counselors as social workers who deal directly with this issue. Counseling and psychotherapist services are one of the important points in problem solving. Related conditions that need attention are the paradigm and attitude of the students themselves against the LGBTQ phenomenon.